From SIGNALS to success? The effects of an online advising system on course grades. Issue 6 (2nd November 2019) - Main, Joyce B.; Griffith, Amanda L.
ABSTRACT: Online advising tools have the potential to reach a large number of students with the goal of increasing course performance and learning with relatively modest time investment from the instructor. Course SIGNALS provides students with online, real-time feedback on course performance based on an algorithm using the student's effort, achievement, academic history, and demographic characteristics. Using roughly 25, 000 student-course level observations from a large, research-intensive university in the Midwest, results from fixed effects difference-in-differences models indicate that SIGNALS helps improves grades of lower-achieving students and decreases the probability that students will fail the course.